2016
DOI: 10.1016/j.jcrimjus.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Childhood and adolescent risk and protective factors for violence in adulthood

Abstract: Purpose We use data from a community sample followed from ages 8 to 48. We focus on the main and risk-buffering effects of childhood and adolescent protective factors for predicting adulthood violence (official records and self reports). Method Males (N=436) from the Columbia County Longitudinal Study participated. The youth, their parents, and peers were first interviewed when the youth were age 8; the youth were later interviewed at ages 19, 30, and 48. Results Risk factors for adulthood violence include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 35 publications
1
35
0
4
Order By: Relevance
“…We had hypothesized that such changes could translate into stress and distraction in parents’ lives, making them less able to parent in ways that limit young people's exposure to violence (e.g., Osborne & McLanahan, ). Family structure changes could also play a role in the degree to which young people disclose risk to parents as well as how they spend their time and with whom (Dubow et al., ; Smetana, ). Together, these shifts in parent and youth behavior and the parent–youth relationship during adolescence could contribute to young people's exposure to violence.…”
Section: Discussionmentioning
confidence: 99%
“…We had hypothesized that such changes could translate into stress and distraction in parents’ lives, making them less able to parent in ways that limit young people's exposure to violence (e.g., Osborne & McLanahan, ). Family structure changes could also play a role in the degree to which young people disclose risk to parents as well as how they spend their time and with whom (Dubow et al., ; Smetana, ). Together, these shifts in parent and youth behavior and the parent–youth relationship during adolescence could contribute to young people's exposure to violence.…”
Section: Discussionmentioning
confidence: 99%
“…Urban informal settlements have been associated with high levels of poverty, crime and violence, poor health outcomes-including HIV/AIDS-as well as poor access to basic services such as schools and health care facilities. Past studies have found strong association between violence experience and poverty at the household [9,12] and community levels [9,13,14], a major characteristic of the urban informal settlements.…”
Section: Plos Onementioning
confidence: 99%
“…Many factors associated with gender likely contribute to this difference, but biological differences and perceptions of control or power associated with masculinity norms may contribute (Kimmel & Mahler, 2003). Aggressive behavior early in childhood. One of the most consistent findings of longitudinal research conducted over the past 50 years has been that early aggressive behavior predicts later aggressive, antisocial, violent, and criminal behavior (Dubow, Huesmann, Boxer, & Smith, ; Dubow, Huesmann, Boxer, & Smith, ; Dubow, Huesmann, Boxer, Smith, & Sedlar, in press; Huesmann, Eron, & Dubow, ; Huesmann, Eron, Lefkowitz, & Walder, ). In other words, children displaying more physically aggressive behavior are more likely to grow up to be adults displaying more violent behavior. Personality and emotion regulation.…”
Section: Personal Risk Factors For Youth Violencementioning
confidence: 95%